Understanding the Strategy and Practical Solutions to Prevent Crimes in the Field of Groundwater Resources and Reduce the Effects of Water Crisis in Kurdistan Province - Jahedeh Tekyekhah; Shler Katorani; Sirvan Seidi; Chia Sohrab Nejad; Milad Jafari (محیط زیست و مهندسی آب)
One of the challenges of the world today is the water shortage crisis. With the occurrence of droughts and indiscriminate harvesting of water reserves, the livelihood of local communities has faced critical conditions. The purpose of this research was to know some crimes related to water and the main causes and factors of committing crimes and finally practical strategies to deal with them. In order to determine the amount of factors affecting the commission of water crimes by using the oral judgment of research experts and pairwise comparison of the main indicators measured in the region, the relative weight of each indicator is determined by Expert Choice software, then strategies to reduce the water crisis and achieve sustainable development was presented. The results showed that the economic index and then the management index with relative weights equal to 0.334 and 0.263 respectively have the most importance in committing crimes in the water area in Kurdistan province, Iran. Finally, management strategies and requirements were presented to reduce the effects of water crisis. The main emphasis of this research is on increasing investments and economic issues in the discussion of water resources.